The Performance Impact of Core-Component Outsourcing: Insights from the LCD TV Industry. (August 2021) - Viswanathan, Madhu; Mukherji, Prokriti; Narasimhan, Om; Chandy, Rajesh
Firms in technology markets often outsource the manufacture of core components—components that are central to product performance and comprise a substantial portion of product costs. Despite the strategic importance of core-component outsourcing, there is little empirical evidence (and many conflicting opinions) about its impact on consumer demand. The authors address this gap with an examination of panel data from the flat panel TV industry, across key regions globally. Results from their estimation indicate that core-component outsourcing reduces the firm's ability to be on the technological frontier; this hurts demand, because the authors' estimates suggest that consumers care about firms being on the frontier. However, such outsourcing also reduces costs. Finally, the authors find that outsourcing increases the intensity of competition in the marketplace. They assess these (often opposing) effects and conduct thought experiments to quantify the performance impact of core-component outsourcing.